PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP PENURUNAN TINGKAT PERILAKU KEKERASAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT SAKIT JIWA DAERAH SURAKARTA - Djoko Witojo; Arif Widodo (Jurnal Berita Ilmu Keperawatan, 2008)
schizophrenia patient with hardness behavior at patient schizophrenia at psychopath hospital of the make-up of its amount, and get ordered execute which is kinds of- kinds of with medication, column insulation, cordage, and form critical team. From here human aspect by comprehensive likely less is getting of attention in its execution. Therapeutic communications try to become bridge which can lay open cause and give solution of is way of constructive marang without destroy others and environment. Target of: This research aim to know therapeutic communications influence to behavioral degradation hardness behavior at schizophrenia patient at home Psychopath Area Surakarta. Method research use design experiment true, with pretest type control design group. Intake of Sample by using non sampling purposive type sampling probabiility matching with inklusi. Result criteria: result of research, indicating that: with value test Paired t test there are behavioral degradation of hardness at schizophrenia patient at treatment group and group control by significant. And percentage only there is difference equal to mean value 6 % among two groups. and Value difference between group control and this treatment group in test by using is Independent of t Test discovered by value 0,324, this value is compared to smaller of p significant value 0,05 meaning the result have a meaning of or significant. This matter answer hypothesizing early, meaning there is influence applying of therapeutic communications to behavioral degradation of hardness.